Synthesis and characterization of biobased poly(butylene succinate-ran-butylene adipate). Analysis of the composition-dependent physicochemical properties. (February 2017) - Debuissy, Thibaud; Pollet, Eric; Avérous, Luc
Graphical abstract: Highlights: High molar mass poly(butylene succinate- ran -butylene adipate) copolyesters syntheses from renewable resources. Excellent thermal stability with degradation profiles driven by the diacid major component. Isodimorphic co-crystallization behavior. Presence of both crystalline phases for adipate contents of 50–60 mol.%. Decrease of Tg with the adipate content according to the Gordon-Taylor equation. Abstract: Fully biobased aliphatic random poly(butylene succinate- ran -butylene adipate) (PBSA) copolyesters and the corresponding homopolyesters (poly(butylene succinate) (PBS) and poly(butylene adipate) (PBA)) with high molar mass, were synthesized with different succinic acid/adipic acid (SA/AA) molar ratio by transesterification in melt, using titanium (IV) isopropoxide as an effective catalyst. All synthesized copolyesters were fully characterized by various chemical and physicochemical techniques including NMR, SEC, FTIR, WAXS, DSC and TGA. The final copolyesters molar compositions were identical to the feed ones. The different sequences based on succinate and adipate were randomly distributed along the chains. All the corresponding copolyesters showed an excellent thermal stability with a degradation onset temperature higher than 290 °C and a thermal degradation profile driven by the major diacid component. Glass transition temperatures of copolyesters decreased with the adipate content due to the decrease of the chain mobility, following the Gordon-Taylor relation. PBSA showed a pseudo-eutectic melting behavior characteristic of an isodimorphic character. Besides, the presence of both crystalline phases was observed for adipate content in the range 50–60 mol.%.